Efeito de elementos substitucionais e intersticiais na microestrutura, dureza e módulo de elasticidade de ligas Ti-Nb - Silva, Luciano Monteiro da [UNESP] (2014)
Recent scientific advances have led to a significant increase in life's quality and consequantly, longevity. As a result, the elderly population has increased considerably and thus age-related diseases such as osteoporosis lead the government to spend considerable sums of money with orthopedic prostheses. There is also a great demand for orthopedic prostheses due to accidents. The most used Ti-based alloy for biological applications is the Ti-6Al-4V alloy, but some studies associate the V to cytotoxic effects and adverse reactions in tissues , while Al has been associated with neurological disorders. To solve this problem, new Ti-based alloys that have in their composition elements such as Nb, Ta, Zr, Fe and Mo are being researched. The development of new Ti-based alloys containing Nb for orthopedic application is a topic of great social and technological relevance, as this element is a non-toxic, non-allergenic, has high biocompatibility and has Brazil as its biggest producer, hence the importance of development of science and technology using this material. The processing steps, the concentration of substitutional solute and the presence of interstitial elements (O, C, N and H) changes signficantly the mechanical properties of the alloy, particularly its elastic properties, causing hardening or softening of the alloy. This work presents the effects of processing steps, the concentration of interstitial oxygen and niobium in solid solution in some mechanical properties of alloys of Ti-NB system, prepared by arc melting and characterized by density measurements, X-ray diffraction, optical microscopy, Scanning Electron Microscopes, microhardness, quantitative chemical analysis, analysis of the oxygen content and modulus of elasticity. Observed trend of increasing oxygen content, while increasing in the niobium content tends to stabilize the B phase, which presents values lower of elasticity modulus than the presented by the a phase